The knowledge, attitudes and practices (KAP) of correctional officers relating to HIV and AIDS in Johannesburg Management Area: Gauteng Region: Republic of South Africa - Baloyi, Risimati Solidify (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.